The Effect of Trehalose Supplementation on Macrovascular Inflammation Biomarker in Old Rats by Assessing NFκB-p65 Expression - Inggrid -; Aminuddin -; Arif Santoso; Nurpudji A Taslim; Ika Yustisia; Irfan Idris (Amerta Nutrition, 2022)
Background: Vascular inflammation is one of contributing factors to the pathogenesis of arterial aging. Age-related activation of the inflammatory process can lead to various macro-and microvascular pathologies. The pro-inflammatory microenvironment generated in the vascular wall can lead to the pathogenesis of vascular diseases due to an increase in vascular dysfunction. Trehalose is a disaccharide that has several functions, protecting against stressors (one of them is reactive oxygen species/ROS) and preventing the inflammatory responses induced by endotoxic shock. Objectives: To analyze the effect of trehalose supplementation on macrovascular inflammatory processes related to the aging process. Methods: The experimental study used 28 male Wistar rats (Rattus novergicus) which were divided into 4 groups, young control group (Group A), old control group (Group B), 2% sucrose group (Group C), and 2% trehalose group (Group D); were then observed for 8 weeks. Results: The results showed that there were no significant differences in aortic tissue NFκB-p65 expression between old and young subjects (p=0.247). The 2% trehalose group had 40% lower aortic tissue NFkB-p65 expression compared to the old control group (p=0.012); while the group given 2% sucrose solution had a 30% higher aortic tissue NFkB-p65 expression compared to the trehalose group (p=0.018). Conclusion: Trehalose has a good effect on aging-associated vascular inflammatory processes that can be seen from the low aortic tissue NFκB-p65 expression in old rats.